Behavioural perspective of tobacco use among youth of Vidarbha region of Maharashtra state in central part of India - Gaikwad, Rahul Narayan (Brazilian Dental Science, 2019)
Objective: This study was conducted to find out the youth perspective about the use of tobacco and its ill effects. The survey was conducted at a private Engineering college of Nagpur, Maharashtra India. Material and Methods: A cross-sectional study with self-administered modified Global youth tobacco survey (GYTS) questionnaire was used for data collection. Eight hundred nine college students of age group between 17 year-24years were included in this study. The questionnaire comprised of information on socio-demographic characteristics and questionnaire was used to gather data on knowledge, attitude and practices of participants about tobacco use. Data analysis was performed by using chi-square test and Statistical significance was measured at a level of 0.05. Result: Out of 806 total participants, 136 (16.8) were current tobacco consumers, significantly high prevalence of tobacco use was observed among boys 106 (13.1) than girls 30 (3.7). Moreover, a higher number of boys 106 (13.1) started smoking at young adolescent age (13- 20 years) than girls30 (3.7). Conclusion: The findings in the study suggest that tobacco use is still an important risk behavior amongst students. Tobacco use was comparatively higher amongst boys though its use is not restricted to them only. There is a need to plan to gather nationwide baseline data on the use of tobacco by young adolescents and the factors associated with initiation of tobacco habit. Keywords Global youth tobacco survey (GYTS); Tobacco prevalence; Tobacco use among youth.